Between Women: Female Health Workers and the Struggle to Transform Diets in Rural Mexico, 1920-1960 - Aguilar Rodríguez, Sandra (Jahrbuch für Geschichte Lateinamerikas, 2023)
This article explores food and foodways in Mexico through the analysis of nutrition discourses and the experience of a visiting nurse in the state of Guanajuato in the middle of the twentieth century. After the Mexican revolution there was an increased interest in changing the diet of the poor. The idea behind nutrition discourses was that a better diet would improve the health and productivity of workers, and eventually boost their earnings. Understandings of good nutrition were influenced by eugenics and the discourse of mestizaje, which materialized in welfare programs. Women played a key role as they were responsible for implementing these programs as well as the main target of them. The experience of a visiting nurse reveals gender and social class dynamics as well as negotiations needed to implement state programs. It also shows the limited success of state policy as it was unable to address the main problems: lack of resources and access to basic services. Eventually peasant and working-class diet changed as a result of increased processed food consumption, having a negative impact on the health of most Mexicans.
Keywords: Nutrition; Gender; Social Class; Visiting Nurses; Cooking; Peasants